2020
DOI: 10.21203/rs.3.rs-49590/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health and Marital Satisfaction Changes of Pregnant and Lactating Women During the COVID-19 Pandemic

Abstract: Background: Women during pregnancy and in the first year after childbirth are vulnerable to mental disorders in the outbreaks of infectious diseases such as Coronavirus Disease (COVID-19). There is a relationship between mental health and marital satisfaction. This study aimed to assess mental health, anxiety, depression, and marital satisfaction among pregnant and lactating women and compared the results with non-pregnant/lactating (as control group) during the COVID-19 pandemic in Iran.Methods: A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Of the total 29 studies, 10 were excluded due to inconsistency of results. 31 40 Eventually, 19 eligible studies were used in the final analysis of the current systematic review and meta-analysis 41 59 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the total 29 studies, 10 were excluded due to inconsistency of results. 31 40 Eventually, 19 eligible studies were used in the final analysis of the current systematic review and meta-analysis 41 59 ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of total of 19 studies included in the final analysis, four studies were done in Canada, 42 , 47 , 52 , 57 three studies in China, 48 , 50 , 56 two in Iran, 41 , 45 six in European countries (Belgium, 55 United Kingdom, 44 Turkey, 58 Ireland, 51 Bosnia and Herzegovina and Serbia, 46 and Italy 49 ), and the rest were conducted in the United States, 59 Colombia, 53 and Sri Lanka. 54 All studies were cross-sectional studies and critical appraisal of cross-sectional studies conducted revealed that about 95% of studies scored more than 75%, only one scored lowest scored 62.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings imply that the COVID-19 pandemic is a serious challenge for pregnant women. A former study in Iran also showed that pregnant women had higher levels of COVID-19 anxiety compared with their non-pregnant counterparts [ 40 ]. Another study in Iran revealed that pregnant women in the third trimester of pregnancy were concerned with COVID-19 disease and its consequences and had higher levels of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our findings, a former study reported no significant difference in depression rate among pregnant women before and after the SARS outbreak [ 8 ]. A study in Iran also showed no significant difference among non-pregnant, pregnant, and breastfeeding women regarding depression rate during the COVID-19 pandemic [ 40 ].…”
Section: Discussionmentioning
confidence: 99%